Design and Development of an Open-Source ADL-Compliant Prosthetic Arm for Transradial Amputees - Timm, Lara (Department of Human Biology, 2022)
Transradial amputation is traumatic – leading to the amputee having a limited ability to perform activities of daily living (ADLs). Below-elbow prostheses are prescribed. The high cost associated with prostheses results in many amputees in low-to-middleincome countries relying on government subsidised devices, which are cosmetic rather than functional, or none at all. Open-source prostheses have the potential to increase the accessibility of functional prosthetic arms, but at present are not optimised to assist the dominant hand in performing bimanual ADLs. The aim of this study is thus to design and experimentally validate an open-source prosthetic arm that is functionally optimised for the performance of ADLs in the unilateral transradial amputee population. The ADL arm is functional open-source below-elbow prosthesis. This device is bodypowered; featuring a hand terminal device with thumb abduction and adduction, and wrist pronation and supination functionality. Elbow flexion of the residual limb is used to actuate the terminal device. The prosthesis requires no existing prosthetic hardware; and the majority of parts can be 3D printed. The ADL arm is designed to reliably perform the grasps required by the non-dominant hand in two-handed ADL activities. Device validation includes functional and simulated-use components. The functional assessment uses the Anthropomorphic Hand Assessment Protocol (AHAP); while the simulated-use assessment involves a practical ADL verification, and a usability assessment using healthy volunteer participants. The AHAP gives as result a grasping ability score (GAS) and partial GAS for ten grasp types associated with ADLs. The GAS represents the percentage of healthy limb function achievable by the prosthesis. The overall GAS of the ADL arm is found to be 68 %. The ADL arm achieved a partial GAS of greater than 75 % for four of five bimanual ADL grasps. A major design flaw resulted in a partial GAS of 33.3 % for the lateral pinch grasp type. The performance in this grasp, as well as others, would be greatly improved by the inclusion of a mechanism to lock the distal joint of the digits in extension during grasp. In this way, the hand would be better able to apply force to an object with the pads of the digits. Simulated-use validation of the ADL arm is performed on healthy participants using the designed bypass socket. The ADL assessment involves the completion of 86 ADL and instrumental ADL tasks; scored using the designed self-report questionnaire. The participant could perform all but seven tasks independently, and the perceived difficulty for tasks requiring the prosthesis was low overall. Seven healthy volunteers are used to assess the system usability. Participants performed a number of tasks and then completed the system usability scale (SUS). The perceived usability of the device is found to increase with increased device familiarity, yielding an overall score of 84.29. This result indicates that participants found the experience with the device to be ‘good' overall. In conclusion, the ADL arm is functionally competent and has proven its ability to assist in the performance of ADLs in a simulated-use environment; using healthy participants. A number of design modifications are recommended to overcome the limitations of the current design, which should be tested in the transradial amputee population to corroborate the results obtained in this study.